Visitor safety and security compliance as a key component of event planning and implementation? Findings from a German research project on COVID-19 - Schütte, Patricia M.; Schulte, Yannic; Schmitt, Alexandra; Schönefeld, Malte; Barber, Vivien; Fiedrich, Frank (Frontiers in Communications and Networks, 2024)
Introduction: Event Safety and Security Production (ESSP) typically involves event organizers, private security firms, authorities, police, fire brigades, and others. Their joint responsibility is to ensure safety, decide on measures, communicate them, and enforce them when necessary. Effective ESSP relies on visitor cooperation and rule compliance. The COVID-19 pandemic highlighted the importance of rule compliance in event safety and security. With the event industry’s standstill and subsequent reopening under strict conditions, organizers had to implement comprehensive safety and hygiene measures. Studies on crowd compliance under pandemic conditions identified influencing factors. These include perceived threats, sociodemographic characteristics, group behavior, trust in institutions, etc.. Methods: Little research focuses on actively promoting rule compliance. Therefore, this paper addresses three research questions (RQ): (1) To what extent does the compliance of visitor safety measures play a role in the planning and implementation of events? (2) To what extent have visitor safety measures been complied with at events during the pandemic and did that change throughout the pandemic? And finally (3) How can the compliance of measures for visitor safety explicitly be taken into account in event planning and implementation? Qualitative data from 11 expert interviews and quantitative data from a representative population survey (N = 10,239) from a German research project on non-pharmaceutical interventions (NPIs) for the safe reopening of events during the pandemic are used to answer the first two questions (RQ1; RQ2). Results of the data triangulation point to recommendations for practical application (RQ3). Results and Discussion: Findings suggest a high level of compliance with COVID-19 measures among the survey respondents, with expert consensus on the need for active and communicative visitor involvement in the implementation and enforcement of visitor safety measures. These insights extend beyond pandemic-specific events to traditional security and safety measures in crowd management. For event practice, this indicates the importance of consistent, transparent, and engaging communication strategies starting well before the event, with the customer journey approach as a potential solution. Suitable approaches to visitor safety by event organizers should be implementable and enforceable; this is the key to ensuring that event communication in relation to ESSP is effective.